Genetic variation in Tunisia in the context of human diversity worldwide. Issue 1 (18th May 2016) - Cherni, Lotfi; Pakstis, Andrew J.; Boussetta, Sami; Elkamel, Sarra; Frigi, Sabeh; Khodjet‐El‐Khil, Houssein; Barton, Alison; Haigh, Eva; Speed, William C.; Ben Ammar Elgaaied, Amel; Kidd, Judith R.; Kidd, Kenneth K.
ABSTRACT: Objectives: North Africa has a complex demographic history of migrations from within Africa, Europe, and the Middle East. However, population genetic studies, especially for autosomal genetic markers, are few relative to other world regions. We examined autosomal markers for eight Tunisian and Libyan populations in order to place them in a global context. Materials and Methods: Data were collected by TaqMan on 399 autosomal single nucleotide polymorphisms on 331 individuals from Tunisia and Libya. These data were combined with data on the same SNPs previously typed on 2585 individuals from 57 populations from around the world. Where meaningful, close by SNPs were combined into multiallelic haplotypes. Data were evaluated by clustering, principal components, and population tree analyses. For a subset of 102 SNPs, data from the literature on seven additional North African populations were included in analyses. Results: Average heterozygosity of the North African populations is high relative to our global samples, consistent with a complex demographic history. The Tunisian and Libyan samples form a discrete cluster in the global and regional views and can be separated from sub‐Sahara, Middle East, and Europe. Within Tunisia the Nebeur and Smar are outlier groups. Across North Africa, pervasive East‐West geographical patterns were not found. Discussion: Known historical migrations and invasions did not displace or homogenize the genetic variation in the region but rather enriched it. Even a small region like Tunisia contains considerable genetic diversity. Future studies across North Africa have the potential to increase our understanding of the historical demographic factors influencing the region. Am J Phys Anthropol 161:62–71, 2016. © 2016 The Authors American Journal of Physical Anthropology Published by Wiley Periodicals, Inc.